Hume's Radical Scepticism and the Fate of Naturalized Epistemology - Meeker, K. author. aut Link
XIII, 196 p.
Keywords: Treating David Hume as a partner in a continuing philosophical dialogue, this book tries to come to terms with Hume's influential thoughts on scepticism and naturalism in a way that sheds light on contemporary philosophy and its relationship to science.